Molecular cloning, characterization and expression of the [beta]-xylanase cDNA gene XYN3 and arabinofuranosidase cDNA gene ABF2 of aspergillus species in the yeast Saccharomyces Cerevisiae - Crous, Johan Marco (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.